Hubungan Pengetahuan Ibu Hamil Tentang Persalinan Dengan Kesiapan Ibu Hamil Trimester III Dalam Menghadapi Persalinan - sari, kartika; Kiki Wahyuni (Midwifery Science Care Journal, 2023)
Background: Mother's unpreparedness in facing childbirth is one of the factors causing the high maternal mortality rate (MMR) and infant mortality rate (IMR). The occurrence of maternal deaths related to knowledge about childbirth. To determine the relationship between the knowledge of pregnant women about childbirth and the readiness of third trimester pregnant women in facing childbirth at the Leyangan Health Center. Method: The research design is correlational analytic with a cross sectional approach. The population of this study were all third trimester pregnant women who assessed pregnancy at the Leyangan Health Center, the sample studied was 31 people taken using the accidental sampling method. Data collection tool using a questionnaire. Data were analyzed using the Chi Square test which was processed with the SPSS data processing program. Result: Research results show pregnant women in the third trimester had mostly good knowledge about childbirth (51.6%) and had good readiness to face childbirth (51.6%). There is a significant relationship between knowledge about childbirth and readiness for childbirth in third trimester pregnant women at the Leyangan Health Center, East Ungaran District, Semarang Regency, with a p value of 0.000 (α = 0.05). Conclusion: The conclusion of this study is that the better the knowledge about childbirth, the better the readiness that pregnant women have in facing childbirth. Keywords : Knowledge, Preparedness, Childbirth